Mothers respond differently to infants' gestural versus nongestural communicative bids. Issue 4 (August 2013) - Olson, Janet; Masur, Elise Frank
Thirty infants at 1;1 and their mothers were videotaped while playing for 18 minutes. Experimental stimuli were presented in three communicative intent contexts – proto-declarative, proto-imperative, and ambiguous – to elicit infant communicative bids that did and did not contain gestures. Mothers' responses were analyzed, and their verbal responses were further coded as object labels, action labels, internal state labels, and nonlabeling utterances. Results demonstrated differential responses to infants' gestural and nongestural bids. Mothers responded more often and were more likely to provide a verbal response in all contexts when infants' communicative bids included gestures. They were also more likely to provide an object label and less likely to provide nonlabeling utterances to gestural than nongestural bids in the proto-declarative and ambiguous contexts. The privileged responses following infants' gestures may serve as a mechanism for vocabulary acquisition.